Methodenanalyse im Revenue Management. - Frank, Michael; Friedemann, Martin; Schröder, Anika (Deutscher Verkehrs-Verl., 2007)
Als Revenue Management bezeichnet man die Methoden, die die gegebene Sitzplatzkapazität eines Flugzeugs auf die unterschiedlichen Produkte verteilen, um einen maximalen Ertrag zu erzielen. Es gibt hierfür verschiedene Optimierungsmethoden, deren unterschiedliche Wirksamkeit sich in der alltäglichen Nutzung jedoch nicht quantifizieren lässt. Schwerpunkt des Beitrags ist eine Darstellung der Anwendung von stochastischen Simulationen zu diesem Zweck. difu

Clients place different demands on air transport as a service provider, which airlines want to meet with specific service offers and variable tariffs. Revenue management is the term used to describe the methods applied by airlines to divide an aircraft's seating capacity into different classes of service in order to optimize revenue. This form of market segmentation has close links with a carefully balanced product differentiation. Over the years, revenue management has witnessed the development of a range of optimization procedures. A straightforward analysis tends not to pinpoint those methods, which encourage better results. This is why a stochastic simulation process is applied in order to describe the methods available and to facilitate their comparison. This report is focused on the advantage of applying a stochastic simulation process to assist decision-making in revenue management. Special reference is made to the introductory comments made above and to setting up an appropriate case for simulation Several cases are featured to explain methods of evaluation. difu
Keywords: Verkehr; Verkehrsplanung; Luftverkehrsmittel; Management; Preis; Optimierung; Simulationsmodell; Kapazitätsplanung; Sitzplatz; Nachfrageorientierung; Stochastik